INFLUENCE OF THE NOSE SHAPE OF PROJECTILES ON THE PENETRATION CHARACTERISTICS OF ALUMINUM HONEYCOMB SANDWICH PLATES - HU Jing; LU MingJian; ZHANG Yong; ZHANG YinBo (Jixie qiangdu)
The aluminum honeycomb sandwich plates were impacted by the hemispherical-nosed projectiles and the bluntnosed projectiles launched by a one-stage gas gun,and the influence of the nose shape of projectiles on the ballistic limits,the failure mechanisms of the targets and energy absorption efficiency was analyzed.The results show that the ballistic limit of bluntnosed projectile is higher than hemispherical-nosed projectile,and the nose shape of projectile has a significant effect on the failure mode of aluminum honeycomb sandwich plates.The energy absorption efficiency of sandwich target against blunt-nosed projectile impact is significantly higher than hemispherical-nosed projectile,but the difference between the energy absorption efficiency decreases with the increase of the initial kinetic energy.